Migrant orangutan males use social learning to adapt to new habitat after dispersal - Mörchen, Julia; Luhn, Frances; Wassmer, Olivia; Kunz, Julia A.; Kulik, Lars; van Noordwijk, Maria A.; van Schaik, Carel P.; Rianti, Puji; Utami Atmoko, Sri Suci; Widdig, Anja; Schuppli, Caroline (Frontiers in Ecology and Evolution, 2023)
Dispersal has been suggested to be challenging, especially for species that heavily rely on social learning for knowledge acquisition. One of the obstacles that migrants face is learning how to cope with an unfamiliar, new habitat, which may involve learning from resident individuals. So far, only very few studies have looked at social learning in migrants after dispersal. Here we examine how migrant male orangutans use a behavior called “peering” (an indicator of observational social learning), to learn from local individuals. In total, we analyzed 4,009 daily dyadic associations with and without peering events of 77 males of the highly sociable Sumatran orangutans (Pongo abelii) at the Suaq population and 75 males of the less sociable Bornean orangutans (Pongo pygmaeus wurmbii) at the Tuanan population, covering a combined study time of 30 years. Analysis using generalized linear mixed models supported our prediction that migrant males in Suaq preferentially peered at the local adult females. However, in Tuanan, migrants peered mostly at other adult males and local immatures. Migrants’ peering rates were highest shortly after their arrival, and significantly decreased with increasing time spent in the area. Migrants in both sites peered significantly more at peering targets’ feeding on food items that are rarely eaten within the locals’ diet, than at commonly eaten ones and peered significantly more at skill-intense food items than easy-to-process ones. Further, migrants interacted significantly more with the peered-at food item after the peering event, than before, suggesting that they practice the observed behavior. Our results therefore suggest that migrant males use peering to learn new ecological knowledge after dispersal (e.g., where and what to feed on), and continue to learn complex skills even within adulthood, (e.g., how to feed on skill-intense food items). To do so, migrants selectively attend to the most knowledgeable and/or available individuals, practice the new skill afterwards and even flexibly adjust their learning, e.g., when confronted with intolerant locals or when the need for learning decreases. Together, our study provides important evidence that social learning in great apes expands towards adulthood, an ability which critically impacted also human evolution.